KNOW-HOW AS A MEANS OF STIMALATION OF SCIENTIFIC DEVELOPMENTS EMBEDDING - T. L. Dashkevich; L. I. Mastugin; V. A. Hlebtsevich (Литьë и металлургия)
He article is dedicated to the problems of using of the objects of industrial property in production. The role and ways of adaptation of scientific developments (knowhow) to the modem conditions are described, the questions of their registration and certification for commercialization and widening of possibilities of know-how using